Postapokaliptyczne role ludzi i roślin w grze Cloud Gardens. Czym jest ogród? - Zaborowski, Karol (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This article is concerned with the fate of trash and plants which grow on it. As an example of this, the video game Cloud Gardens was chosen, along with installation arts by Elżbieta Rajewska and Diana Lelonek. The paper analyzes the process of creating landscapes known from popular works of post-apocalyptic fiction; what in other titles is only a background to events and human tragedy is of greatest importance here. Later parts of the article discuss human responsibility for the unexpected development of other species, as well as plants’ indifference to the human apocalypse. This text is part of the non-anthropocentric humanism trend and refers to the concept of “plant art” as proposed by Anna Wandzel.